One more way to address the seasonal water shortage of the largest freshwater lake in China? A nature-based solution through lake bathymetry restoration - Bing Li; Guishan Yang; Rongrong Wan; David P. Hamilton; Jing Yao (Journal of Hydrology: Regional Studies)
Study region: Poyang Lake, the largest freshwater lake in China, is a critical water resource and ecological hub. However, seasonal dryness has raised significant concerns about the sustainability of its hydrological regime. Study focus: This study investigates the potential of morphological restoration as a nature-based solution to mitigate Poyang Lake’s seasonal water shortages. A hydrodynamic model simulated water level, depth, and velocity changes under four scenarios where the lakebed morphology of three severely incised areas was restored to 1998 conditions. The simulations evaluated the hydrodynamic impacts of restoration, focusing on its implications for water resource management and ecological functions. New hydrological insights for the region: Results revealed significant impacts of bathymetry restoration, particularly during low-water-level periods. Water depth in the upstream main channel increased by 0.5–2.5 m and by 0.1–0.5 m in the floodplain during the dry season. Water velocity showed contrasting trends, decreasing by 0.01–0.1 m/s in the main channel and increasing by 0.01–0.1 m/s in the floodplain. Nonlinear correlations between water depth increases and baseline water levels highlighted the most pronounced effects during dry seasons. The study demonstrates that bathymetry restoration may be a promising strategy for addressing water shortages in the dry season. However, trade-offs among multiple ecosystem services and an optimization procedure should be used in future to select the different opportunities for restoration planning.